Software-Defined Batteries. - Badam, Anirudh; Chandra, Ranveer; Dutra, Jon; Ferrese, Anthony; Hodges, Steve; Pan Hu; Meinershagen, Julia; Moscibroda, Thomas; Priyantha, Bodhi; Skiani, Evangelia (Communications of the ACM, 2016)
Different battery chemistries perform better on different axes, such as energy density, cost, peak power, recharge time, longevity, and efficiency. Mobile system designers are constrained by existing technology, and are forced to select a single chemistry that best meets their diverse needs, thereby compromising other desirable features. In this paper, we present a new hardware-software system, called Software Defined Battery (SDB), which allows system designers to integrate batteries of different chemistries. SDB exposes application programming interfaces (APIs) to the operating system, which controls the amount of charge flowing in and out of each battery, enabling it to dynamically trade one battery property for another depending on application and/or user needs. Using microbenchmarks from our prototype SDB implementation, and through detailed simulations, we demonstrate that it is possible to combine batteries which individually excel along different axes to deliver an enhanced collective performance when compared to traditional battery packs.